1997
DOI: 10.1159/000185432
|View full text |Cite
|
Sign up to set email alerts
|

Final Height of Girls with Central Precocious Puberty, Untreated versus Treated with Cyproterone Acetate or GnRH Analogue

Abstract: This study was designed to determine the benefit of therapy on final height (FHt) in girls with central precocious puberty (CPP). A total of 102 patients were evaluated – 28 untreated, 26 treated with cyproterone acetate (CyA), and 48 treated with GnRH analogue (GnRHA) – and their achieved FHt was compared to the respective target height (THt). Of the untreated girls, half (14/28) had a slow course of puberty and reached THt ± 0.5 SD (FHt 160.2 ± 7.1, THt 159.5 ± 6.6 cm); the other half (14/28) had an accelera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
110
1
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(119 citation statements)
references
References 24 publications
6
110
1
2
Order By: Relevance
“…BA is used to predict adult height by the Bayley-Pinneau method (40), although this method has low accuracy. Bayley-Pinneau tables for average BA should be preferred over those that use accelerated BA, since the latter overestimate adult height (41,42). Pelvic ultrasonography is not used in the diagnosis of precocious puberty, but in girls, it helps determine the uterine and ovarian volume, and is a sensitive method to detect cysts and neoplastic lesions.…”
Section: Imagingmentioning
confidence: 99%
“…BA is used to predict adult height by the Bayley-Pinneau method (40), although this method has low accuracy. Bayley-Pinneau tables for average BA should be preferred over those that use accelerated BA, since the latter overestimate adult height (41,42). Pelvic ultrasonography is not used in the diagnosis of precocious puberty, but in girls, it helps determine the uterine and ovarian volume, and is a sensitive method to detect cysts and neoplastic lesions.…”
Section: Imagingmentioning
confidence: 99%
“…The great majority of patients reached an adult height consistent with the TH (13,14,15,17,18,19,20,21,22,23,24,25), a minority of them did not reach the TH (19,26), and a very small portion of patients remained shorter than the predicted height before treatment (13,27). Discordant results were obtained when comparing the efficacy of treatment in females and males.…”
Section: Adult Heightmentioning
confidence: 81%
“…In a study by Klein et al (24) performed in 98 patients (F:MZ80:18) treated with histrelin or deslorelin, the average adult height and HG (14.5G9.9 cm vs 6.8G6.9 cm; P!0.001) were greater in girls with puberty onset !6 years of age than those with onset of puberty between 6 and 8 years of age. Few studies (12,26) showed no correlation between HG and age at puberty onset or initiation of treatment, suggesting that girls with late onset CPP benefit from treatment similarly to girls with earlier pubertal onset (12). A longer treatment duration appears to be a positive outcome predictor in the majority (19,20,21,24,30), although not all (15,23), of the studies, together with a short interval between pubertal onset and the start of treatment (24,30), a great growth spurt after the end of treatment (12), low pre-treatment estradiol levels (30), and advanced BA at the start of treatment (14,18,19,20,21,25).…”
Section: Adult Heightmentioning
confidence: 99%
“…The use of bone ages is insufficiently reliable, particularly when skeletal maturation is markedly advanced at presentation. Nevertheless, the use of Bayley and Pinneau tables for average children appears to be the preferred methodology for height prediction (30).…”
Section: Effect Of Gnrha Treatment On Final Heightmentioning
confidence: 99%